(untitled) - Nesbit, Edith (Đồng Nai, 2009)
While playing in a gravel pit near their new home, five children come across a Psammead, or sand fairy. The sand fairy is compelled to grant the children one wish per day, and since the children ask for such fantastic wishes, they do not turn to stone at sundown as wishes of the past did. Through these wishes, the children have many magical adventures. In this book, the children, Cyril, Anthea, Robert, Jane and the Lamb begin their trilogy of adventures.
Keywords: English language,Children,Ngôn ngữ tiếng Anh,Trẻ em; Readers,Người thích đọc sách